Tobramycin and Amikacin Delay Adhesion and Microcolony Formation in Pseudomonas aeruginosa Cystic Fibrosis Isolates - Olivares, Elodie; Badel-Berchoux, Stéphanie; Provot, Christian; Jaulhac, Benoît; Prévost, Gilles; Bernardi, Thierry; Jehl, François (Frontiers in Microbiology, 2017)
Cystic fibrosis (CF) patients are predisposed to chronic colonisation of the major airways by P. aeruginosa biofilms. Pulmonary infections, involving sessile bacteria, are the main cause of morbidity and mortality. As the eradication of antibiotic-resistant biofilms remains impossible, one key objective for the treatment of lung infections is to delay the switch of P. aeruginosa to a sessile phenotype. Few tools are currently available in hospital laboratories to evaluate the susceptibility of adherent microorganisms to antimicrobials. In this study, we used the Biofilm Ring Test®, for the achievement of Antibiofilmograms® on CF clinical isolates. In comparison to standard antibiograms, these procedures allow the investigation of antibiotic effects on the biofilm formation by bacteria. To confirm the inter-assay reproducibility, conventional Crystal Violet assays were performed. To mimic the pathologic reality of CF, we also used a model allowing the biofilm growth on CF-derived cells. Results obtained from these three different assays showed that amikacin and tobramycin, the two favoured aminoglycosides in CF therapies, were able to prevent the early adhesion of P. aeruginosa isolates. This promising inhibitory effect of antimicrobials confirm that biofilm setting up is governed by adaptive responses and depends on environmental conditions, as opposite processes of biofilm induction by aminoglycosides were previously described in literature. Finally, Antibiofilmograms®, whose given results are in concordance with other in vitro antibiotic susceptibility testing, appear to be useful for the optimisation of CF therapies by the selection of antimicrobials able to delay chronic infection establishment.